The Exchange of Energy, Water and Carbon Dioxide between Wet Arctic Tundra and the Atmosphere at the Lena River Delta, Northern Siberia - Kutzbach, Lars (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2006)
The ecosystem-scale exchange fluxes of energy, water and carbon dioxide (CO2) between wet arctic tundra and the atmosphere were investigated by the micrometeorological eddy covariance method. The investigation site was situated in the centre of the Lena River Delta in Northern Siberia (72°22'N, 126°30'E). The micrometeorological campaigns were performed from July to October 2003 and from May to July 2004. The combined datasets of the two campaigns were used to characterise the seasonal course of the energy, water and CO2 fluxes and the underlying processes for the synthetic measurement period May 28…October 21 2004/2003 which included the period of snow and soil thawing as well as the beginning of refreezing. The cumulative summer (June…August) energy partitioning was characterised by low net radiation (607 MJ m-2), large ground heat flux (163 MJ m-2), low latent heat flux (250 MJ m-2) and very low sensible heat flux (157 MJ m-2) compared to other tundra sites. These findings point out the major importance of the very cold permafrost (due to extreme winter cooling) for the summer energy budget of the tundra in Northern Siberia. Despite a high cumulative precipitation of 201 mm during summer, the cumulative summer evapotranspiration of 98 mm was low compared to other tundra sites. In summer 2003, heavy rainfall initiated severe thermoerosion phenomena and in the consequence increased drainage and run-off at the wet polygonal tundra thus demonstrating the sensitivity of permafrost landscapes to degradation by changes in hydrology. The CO2 budget of the wet polygonal tundra was characterised by a low intensity of the main CO2 exchange processes, namely the gross photosynthesis and the ecosystem respiration. The gross photosynthesis accumulated to -432 g m-2 over the photosynthetically active period (June…September). The ecosystem respiration accumulated to +327 g m-2 over the photosynthetically active period, which corresponds to 76 % of the magnitude of the gross photosynthesis. The wet polygonal tundra of the ...